Impacts of glacier and sea ice melt on methane pathways on the Northeast Greenland shelf - Verdugo, Josefa; Damm, Ellen; Schaffer, Janin; Bauch, Dorothea; Meyer, Hanno; Kaiser, Jan (Continental shelf research, 2022)
Global warming has led to a sharp decrease in Arctic summer sea ice extent and a dramatic ice mass loss of the Greenland Ice Sheet over the past three decades. The Northeast Greenland continental shelf is a site of intense water mass transformation involving both sea ice processes and glacier dynamics. The Arctic shelf waters are considered to be a net source of atmospheric methane (CH4); however, the effect of glacier and sea ice melt on oceanic CH4 concentrations still needs to be investigated. To better understand the effect of meltwater on the CH4 budget of the ocean, our study constrains the CH4 pathways by following changes in water mass properties and infers potential CH4 sources and sinks. Based on measurements of concentration and carbon isotope delta (δ13C) of CH4, the water mass tracer δ18O(H2O) and physical properties of the water masses, we detected CH4 excess in surface waters, which we attribute to brine release during sea ice formation. We show that this CH4 excess is sustained throughout the melt season, due to a freshwater lid formed at the ocean surface. The meltwater hardly alters the CH4 excess, but enhances water stratification, which, in turn, restricts the sea-to-air flux. The CH4 excess is subject to mixing with surrounding shelf waters influenced by basal glacial meltwater discharge. We suggest that the CH4 excess of Northeast Greenland continental shelf waters is redistributed in the marine environment, while CH4 emission to the atmosphere is limited to regions not covered by sea ice. •CH4 excess is detected in water masses interacting with sea ice.•CH4 excess in surface waters is sea ice-sourced.•The meltwater layer restricts the sea-to-air flux via increased stratification.•CH4 excess is redistributed in the marine environment.•In water masses transported to the shelf, CH4 oxidation acts as biological CH4 sink.